Kenya's Infrastructure : A Continental Perspective - Briceno-Garmendia, Cecilia M.; Shkaratan, Maria (World Bank, Washington, DC, 2017)
This study is a product of the Africa Infrastructure Country Diagnostic (AICD), a project designed to expand the world's knowledge of physical infrastructure in Africa. The AICD provides a baseline against which future improvements in infrastructure services can be measured, making it possible to monitor the results achieved from donor support. It also offers a solid empirical foundation for prioritizing investments and designing policy reforms in Africa's infrastructure sectors. The AICD is based on an unprecedented effort to collect detailed economic and technical data on African infrastructure. The project has produced a series of original reports on public expenditure, spending needs, and sector performance in each of the main infrastructure sectors, including energy, information and communication technologies, irrigation, transport, and water and sanitation. The focus of the AICD country reports is on benchmarking sector performance and quantifying the main financing and efficiency gaps at the country level. These reports are particularly relevant to national policy makers and development partners working on specific countries. This report presents the key AICD findings for Kenya, allowing the country's infrastructure situation to be benchmarked against that of its African peers. Given that Kenya is a relatively well-off low-income country that aspires to become a middle-income country, two sets of African benchmarks will be used to evaluate Kenya's situation. Detailed comparisons will also be made with immediate regional neighbors in the East African community.